2018
DOI: 10.3389/fgene.2018.00602
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol’s Effect on Coq7 Expression in the Hippocampus of Mice

Abstract: Coenzyme Q (CoQ) is a well-studied molecule, present in every cell membrane in the body, best known for its roles as a mitochondrial electron transporter and a potent membrane anti-oxidant. Much of the previous work was done in vitro in yeast and more recent work has suggested that CoQ may have additional roles prompting calls for a re-assessment of its role using in vivo systems in mammals. Here we investigated the putative role of Coenzyme Q in ethanol-induced effects in vivo using BXD RI mice. We examined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The BXD Family Is the Largest and the Most Deeply Phenotyped Mammalian Genetic Reference Panel Data sets for the BXD encompass multiple levels-from single molecules to complex behavioral repertoires and to traits measured with environmental perturbations, including exposure to alcohol and drugs of abuse (Dickson et al, 2019;Mulligan et al, 2018;Thé berge et al, 2019;Zhou et al, 2018), infectious agents (Boon et al, 2014;Chella Krishnan et al, 2016;Russo et al, 2015), dietary modifications (Fleet et al, 2016;Jha et al, 2018bJha et al, , 2018aJones and Jellen, 2017;Reyes Fernandez et al, 2016;Rodrigues et al, 2017), stress (Diessler et al, 2018;Jung et al, 2017), and even as a function of age (Sandoval-Sierra et al, 2020;Williams et al, 2020). This phenome is linked to over 500 publications, including state-of-the-art proteome, metabolome (Williams et al, 2018(Williams et al, , 2020, epigenome (Baker et al, 2019;Sandoval-Sierra et al, 2019), and metagenome (Perez-Munoz et al, 2019) data sets available on GeneNetwork.org.…”
Section: Improved Power and Precision Of Mapping Bxd Phenotypes-a 50-year Path Of Progressmentioning
confidence: 99%
“…The BXD Family Is the Largest and the Most Deeply Phenotyped Mammalian Genetic Reference Panel Data sets for the BXD encompass multiple levels-from single molecules to complex behavioral repertoires and to traits measured with environmental perturbations, including exposure to alcohol and drugs of abuse (Dickson et al, 2019;Mulligan et al, 2018;Thé berge et al, 2019;Zhou et al, 2018), infectious agents (Boon et al, 2014;Chella Krishnan et al, 2016;Russo et al, 2015), dietary modifications (Fleet et al, 2016;Jha et al, 2018bJha et al, , 2018aJones and Jellen, 2017;Reyes Fernandez et al, 2016;Rodrigues et al, 2017), stress (Diessler et al, 2018;Jung et al, 2017), and even as a function of age (Sandoval-Sierra et al, 2020;Williams et al, 2020). This phenome is linked to over 500 publications, including state-of-the-art proteome, metabolome (Williams et al, 2018(Williams et al, , 2020, epigenome (Baker et al, 2019;Sandoval-Sierra et al, 2019), and metagenome (Perez-Munoz et al, 2019) data sets available on GeneNetwork.org.…”
Section: Improved Power and Precision Of Mapping Bxd Phenotypes-a 50-year Path Of Progressmentioning
confidence: 99%
“…( 18,23 ) Patients with alcoholic cirrhosis have the alterations in the level of CoQ, the mitochondrial respiratory chain carrier and a potent membrane anti‐oxidant. ( 19,24 ) The observation may be related to the changes in the inflammatory cytokines, leading to the depletion of CoQ in these patients. ( 25,26 ) Alcohol metabolism causes the accumulation of ROS products and intracellular oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Some animal model studies found negative association between alcohol and cognition mediated by reductions in cell density in the cerebral cortex [ 102 ] and alterations of cholinergic interneurons in the Nucleus Accumbens [ 103 ]. Other animal model studies suggested positive association between alcohol and cognition thought to be mediated by enhancement of brain metabolite clearance [ 104 ] and activation of the vagus nerve [ 105 ], antioxidant system [ 106 , 107 , 108 , 109 ], and other biological processes [ 110 , 111 , 112 ]. However, none of these findings have thus far been confirmed to be causally important.…”
Section: Discussionmentioning
confidence: 99%